Numerical Methods Comparison of Shock-Induced Separation on Transonic Axisymmetric Hump - Miao Zhang; Zhuoyue Tian; Songxiang Tang; Ziyan Wei; Jie Li (Applied Sciences)
A transonic hump with a Mach number (M∞) of 0.875 was utilized to compare the prediction capabilities of RANS, URANS, IDDES, and IDDES-SLA for shock-induced separation. The results matched the experimental data concerning pressure, friction coefficients, velocity distribution, and other parameters. The improved delayed detached eddy simulation with a modified sub-grid scale (IDDES-SLA) method performed the best amongst tested numerical methods, demonstrating differences of 1.3% and 4.1% from the experimental results for separation and reattachment locations, respectively. The primary difference between IDDES and IDDES-SLA is reflected in detailed data, such as velocity and high-frequency characteristics, although both methods exhibit similar simulation capabilities for the main structural features of the flow field. The POD and PSD analyses of the flow field results demonstrated that the IDDES-SLA method was more capable of resolving higher modes of flow field.